(untitled) (International journal of artificial intelligence, 2026)
This article examines the defensive system of ancient Khorezm fortresses and analyzes their military-strategic significance. Special attention is given to the architectural and engineering features of the fortifications, including walls, towers, gates, and construction materials adapted to the local environmental conditions. The study highlights the stages of development of defensive structures in Khorezm, from simple early fortifications to a complex and integrated defense network. The role of major fortresses such as Ayaz Kala and Toprak Kala is considered within the broader context of territorial protection, control of trade routes, and consolidation of political power. The article also explores the importance of Khorezm’s location along the Silk Road, which necessitated the development of advanced defensive strategies. Furthermore, the research is based on archaeological findings and scholarly works, including studies conducted by Sergey Tolstov. The results demonstrate that the defensive system of ancient Khorezm was one of the most advanced military engineering achievements of its time, reflecting a high level of socio-political organization and strategic planning.